2018
DOI: 10.1002/pi.5666
|View full text |Cite
|
Sign up to set email alerts
|

Porous poly(vinyl formal) foam prepared using poly(vinyl alcohol) of low degree of polymerization

Abstract: Poly(vinyl formal) (PVF) foams are usually prepared using poly(vinyl alcohol) (PVA) of high degree of polymerization, the most reported degree of polymerization being 1700. In the work reported, PVA of low degree of polymerization of 500 was used to prepare PVF foams, which is a great challenge because of the weaker hydrogen bond interaction than that for a higher degree of polymerization. By changing the concentration (from 10 to 20 wt%) of PVA solution, PVF foams were successfully obtained. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…However, the excessive time would cause shrinkage of inner pore due to the further reaction between hydroxyl groups with formaldehyde, resulting in a reduction in expansion ratio and water absorption ratio. These results were similar to Li et al (2018). Moreover, excess cross-link meant the increased viscosity of aqueous foam and deformed pores which meant less energy absorption (Pimpa et al, 2007).…”
Section: Effects Of Raw Materials On Pvfm Propertiessupporting
confidence: 65%
See 2 more Smart Citations
“…However, the excessive time would cause shrinkage of inner pore due to the further reaction between hydroxyl groups with formaldehyde, resulting in a reduction in expansion ratio and water absorption ratio. These results were similar to Li et al (2018). Moreover, excess cross-link meant the increased viscosity of aqueous foam and deformed pores which meant less energy absorption (Pimpa et al, 2007).…”
Section: Effects Of Raw Materials On Pvfm Propertiessupporting
confidence: 65%
“…Besides, Xue et al (2016) suggested that PVA could increase cross-linked zones in the volume unit to decrease the density and porosity of PVFM foam. Meanwhile, smaller porosity usually meant the lower water absorption ability (Li et al, 2018). In this study, the porosity reduced but pore size increased with increasing contents of PVA, which may be resulted from the decreased concentration of pore-forming agent water (Xue et al, 2016).…”
Section: Effects Of Raw Materials On Pvfm Propertiesmentioning
confidence: 60%
See 1 more Smart Citation
“…A method of utilizing water as a pore‐forming agent for the production of open‐cell PVF foams has been reported, with the pore size ranging from 1.9 to 10.4 μm as measured by SEM [19] . It is interest to note that in our earlier work, we prepared a series of PVF foams directly without additives, by using a very high concentration of PVA, which has a low degree of polymerization [20] . Closed‐ and open‐cell structures have both been formed in the PVF foams with a high water absorption capacity reaching 626 wt%, which was close to that of the PVF foams prepared using a PVA with a high degree of polymerization as a pore‐forming agent.…”
Section: Introductionmentioning
confidence: 98%
“…PVOH molecular chains contain a large number of hydroxyl groups and hydrogen bonding, which can be cross-linked with the natural polymer material to form a dense network structure, thus, enhancing the mechanical properties of the composite material [ 28 ]. Therefore, PVOH is widely used as a toughening modification of resin-based materials, such as foams [ 29 ], films [ 30 ], and hydrogels [ 31 ].…”
Section: Introductionmentioning
confidence: 99%